The training of children : a book for young teachers, - Dinsmore, John Wirt (American Book Company, 1912)
"It has long been the desire of the author to prepare, for country and village teachers, a work on the development and training of the mind that would contain the essential facts of psychology so plainly and simply expressed that any person might grasp their meaning without a too frequent appeal to the dictionary. It is possible, or it should be possible, to express the underlying truths of any important science in the everyday language of the people. Many young men and young women who lack both high school and college training are nevertheless not lacking in intelligence. They have the ability to understand any available knowledge that is not expressed in terms with which they are unfamiliar. There are many of this class who are capable of doing and are doing excellent work as teachers; they possess the natural qualities requisite to success and are eager to learn. The main purpose of my earlier volume "Teaching a District School" was to assist the inexperienced to master the technique of teaching. This much having been accomplished there should naturally arise a desire for reliable information concerning the nature and development of the human mind, its needs, its manifestations, its inclinations, and, if possible, its destination. This book is designed to meet such a desire. It does not pretend to be an exhaustive treatise concerning either the nature or the training of the mind. It is intended to furnish sound instruction, based upon well-known and fundamental truths, to those who are engaged in the training of children either in the home or in the common schools. It should also prove valuable as an elementary textbook in high schools, academies, and normal schools. There has been no desire on the author's part to furnish knowledge to those who wish merely to be informed upon the subject but who have no inclination to turn their attainments into practical use. The aim has been, all the way through, not only to supply practical knowledge in plain and simple language but to indicate continually the way to apply it"--Create. (PsycINFO Database Record (c) 2014 APA, all rights reserved).